2021
DOI: 10.21203/rs.3.rs-899571/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing The Grain Yield And Grain Protein Content of Common Wheat (Triticum Aestivum) By Introducing Missense Mutations In The Q Gene

Abstract: Grain yield (GY) and grain protein content (GPC) are important traits for wheat breeding and production; however, they are usually negatively correlated. The Q gene is the most important domestication gene in cultivated wheat because it influences many traits, including GY and GPC. Additionally, Qc1 is an overexpressed Q allele containing a missense mutation in the microRNA172-binding site. The common wheat (Triticum aestivum) mutant S-Cp1-1, which carries Qc1, has a very high GPC and some unfavorable characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Unfortunately, Q c1 is inappropriate for breeding because it leads to decreased grain yields, extreme dwarfism, and the production of compact spikes [ 40 ]. A previous study identified Q c1 -N8 as a new allele derived from Q c1 , with a missense mutation in the sequence encoding the second AP 2 domain [ 50 ]. This new allele reverses the unfavorable agronomic characteristics resulting from Q c1 while also positively affecting GPC and grain yields [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, Q c1 is inappropriate for breeding because it leads to decreased grain yields, extreme dwarfism, and the production of compact spikes [ 40 ]. A previous study identified Q c1 -N8 as a new allele derived from Q c1 , with a missense mutation in the sequence encoding the second AP 2 domain [ 50 ]. This new allele reverses the unfavorable agronomic characteristics resulting from Q c1 while also positively affecting GPC and grain yields [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified Q c1 -N8 as a new allele derived from Q c1 , with a missense mutation in the sequence encoding the second AP 2 domain [ 50 ]. This new allele reverses the unfavorable agronomic characteristics resulting from Q c1 while also positively affecting GPC and grain yields [ 50 ]. Wheat is an important protein source for humans [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMG-based recognition studies produced high accuracy (Huang et al, 2008;Pati et al, 2010;Kim et al, 2014). However, the limitation of using this sensor requires sensors to be integrated directly into the skin (Chen et al, 2013). Therefore, EMG signals could be affected by environmental noise, shifts in electrode positions, or even the loss of electrode sensor contact caused by the moisture between sensors and the skin such as sweating and humidity (Rafiee et al, 2011;Phinyomark et al, 2013;Taborri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%